Sintered body, manufacturing method of sintered body, raw material powder for sintered body, and calcined body
By optimizing the composition of zirconia sintered bodies with stabilizing elements and germanium oxide, high impact resistance is achieved while avoiding ceria-derived coloration, thus maintaining the original color tone of zirconia.
Patent Information
- Application Number
- JP2023183126
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-27
- Filing Date
- 2023-10-25
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2042-12-27
AI Technical Summary
Sintered zirconia bodies with high impact resistance are challenging to produce without ceria-derived coloration, which affects their original color tone.
A sintered body containing zirconia with a stabilizing element and germanium oxide, where the amount of stabilizing element and germanium oxide is optimized to achieve high impact resistance without ceria-derived coloration.
The sintered body exhibits high impact resistance through plastic deformation upon dynamic impacts, suppressing brittle fracture and maintaining the original color tone of zirconia.
Smart Images

Figure 0007662009000006 
Figure 0007662009000007 
Figure 0007662009000008
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered body having high impact resistance and containing zirconia as a main phase, a method for producing the sintered body, a raw material powder for the sintered body, and a calcined body. [Background technology]
[0002] In addition to conventional applications such as grinding media and structural materials, sintered bodies with zirconia as a matrix are being considered for use in decorative applications such as decorative parts for watches, portable electronic devices, automobiles, and home appliances. Sintered bodies used for decorative applications are required to have high strength and high toughness to prevent destruction due to external impact. To date, various sintered bodies with high strength and high toughness have been reported as highly reliable materials.
[0003] In recent years, there have been reports of sintered bodies that, in addition to the characteristics of high strength and high toughness, also have improved fracture resistance when subjected to impacts closer to those used in practical applications.
[0004] However, sintered bodies such as zirconia ceramics are prone to brittle fracture when a dynamic load exceeding the fracture resistance of the material is applied. On the other hand, in sintered bodies that undergo plastic deformation when a load is applied, the impact is absorbed by the plastic deformation before brittle fracture occurs, and the initiation and propagation of cracks can be suppressed, resulting in high impact resistance.
[0005] Patent Document 1 reports a zirconia-alumina composite sintered body obtained by sintering a mixture of zirconia powder containing 3.4-5.0 mol% ceria and 0.7-1.2 mol% yttria and alumina powder. It is described that the sintered body shows an impact mark in a drop ball test (weight: 300 g, height: 350 mm, sample shape: plate shape with length 40 mm × width 30 mm × thickness 2 mm) and has a drop ball strength of 1.2 J or more, showing excellent impact resistance. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Patent Publication No. 2021-91601 Summary of the Invention [Problem to be solved by the invention]
[0007] The sintered body in Patent Document 1 uses ceria. Ceria has a unique color, and when these elements are used, the sintered body has a yellowish color. Therefore, it is difficult to obtain a sintered body that has the original color of zirconia without the color tone derived from ceria.
[0008] An object of the present disclosure is to provide at least one of a zirconia sintered body that is free of coloration derived from ceria and exhibits high impact resistance against dynamic impact due to shock absorption by plastic deformation, a method for producing the sintered body, a raw material powder for the sintered body, and a calcined body. [Means for solving the problem]
[0009] That is, the present invention is as defined in the claims, and the gist of the present disclosure is as follows. [1] A sintered body comprising zirconia containing a stabilizing element and germanium oxide, in which, when the amount of the stabilizing element in the zirconia is X mol % and the amount of germanium oxide is Y mol %, Y / X is 0.35 or more and X+Y is 4.0 or less. [2] The sintered body according to [1], which undergoes plastic deformation when a load is applied. [3] The sintered body according to either [1] or [2], wherein the germanium oxide content is 0.1 mol % or more and 4.0 mol % or less. [4] The sintered body according to any one of [1] to [3], wherein the stabilizing element includes at least one selected from the group consisting of yttrium, calcium, magnesium, ytterbium, and gadolinium. [5] The sintered body according to any one of [1] to [4], wherein the content of the stabilizing element is 0.1 mol % or more and 4.0 mol % or less. [6] Fracture toughness of 6.0 MPa m, measured using the SEPB method specified in JIS R1607 0.5 The sintered body according to any one of the above [1] to [5]. [7] The sintered body according to any one of [1] to [6], which contains alumina. [8] A powder comprising zirconia containing a stabilizing element and germanium oxide, in which, when the amount of the stabilizing element in the zirconia is X mol % and the amount of germanium oxide is Y mol %, Y / X is 0.35 or more and X+Y is 4.0 or less. [9] A calcined body comprising zirconia containing a stabilizing element and germanium oxide, in which, when the amount of the stabilizing element in the zirconia is X mol % and the amount of germanium oxide in the zirconia is Y mol %, Y / X is 0.35 or more and X+Y is 4.0 or less.
[10] A method for producing a sintered body according to any one of [1] to [7], characterized in that the powder according to [8] is sintered at 1100°C or higher and 1500°C or lower for 0.3 hours or higher and 20 hours or lower.
[11] A member comprising the sintered body according to any one of [1] to [7]. Effect of the Invention
[0010] The present disclosure aims to provide at least one of a zirconia sintered body, a raw material powder thereof, a calcined body, and a method for producing a sintered body, which is free from ceria-derived coloration and exhibits high impact resistance by generating shock absorption prior to the occurrence of brittle fracture in response to an impact that exceeds the fracture resistance of the sintered body. [Brief description of the drawings]
[0011] [Figure 1] Schematic diagram showing the state of a drop ball test using a DuPont type drop ball tester [Diagram 2] FIG. 13 is a schematic diagram showing an example of an impact core (formation of a recess) after a ball drop test. [Diagram 3] Schematic diagram showing an example of the vicinity of the impact core after a conventional sintered body is subjected to a ball drop test [Figure 4] Schematic diagram showing an example of the arrangement of measurement samples in a drop ball test [Diagram 5] Schematic diagram showing how to measure the depth of impact marks [Figure 6] Schematic diagram showing an example of the mode of destruction caused by a ball drop test: (a) state where destruction has occurred, (b) state where destruction has not occurred [Figure 7] Appearance of the sintered body of Example 2 after the ball drop test (magnification: 20x, load: 300g, ball drop height: 50cm) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, the sintered body of the present disclosure will be described with reference to an example of an embodiment.
[0013] The sintered body obtained from the powder of this embodiment (hereinafter, also referred to as "the sintered body of this embodiment") has a region that undergoes plastic deformation. An example of the region that undergoes plastic deformation is a region where an impact mark is formed when an impact force is applied. In this embodiment, "plastic deformation" refers to a deformation of the sintered body caused by the application of an external force, which remains in the sintered body after the external force is removed. Therefore, plastic deformation is different from deformation in which no deformation remains after the external force is removed (so-called elastic deformation) and destruction due to the occurrence and progression of defects such as cracks without deformation of the sintered body (so-called brittle destruction). Furthermore, the plastic deformation in this embodiment is also different from the deformation caused by the so-called superplastic phenomenon, which is a phenomenon in which grain boundary sliding occurs continuously when the sintered body is deformed at a constant strain rate in a high temperature range (for example, a temperature range of 800°C or higher), causing elongation. One of the reasons why the impact resistance of the sintered body of this embodiment is improved, that is, why the impact resistance is improved, is that the region that undergoes plastic deformation, such as the region where the impact mark is formed (hereinafter, also referred to as the "plastic deformation region"), exhibits the function of absorbing and dispersing the energy transmitted by the applied impact force. As a result, when an impact force is applied, at least plastic deformation occurs prior to the occurrence of brittle fracture, and as a result, the occurrence of brittle fracture is suppressed and the impact resistance is improved.
[0014] The sintered body of this embodiment may have a plastic deformation region in at least a portion of the sintered body (i.e., may be a sintered body having a plastic deformation region), but may be mainly composed of a plastic deformation region or may be a sintered body composed of a plastic deformation region.
[0015] The term "impact force" refers to a force that transmits energy to a sintered body, particularly a dynamic external force, preferably an external force that exceeds the fracture resistance of the sintered body, more preferably a dynamic external force that exceeds the fracture resistance of the sintered body, and further a dynamic external force that exerts elastic energy on the sintered body.
[0016] "Applying an impact force" means that energy is applied to at least a part of the sintered body, and examples of this include energy being dynamically applied to the sintered body by the sintered body coming into contact with an object, such as the sintered body falling and touching the ground, or a falling object coming into contact with the sintered body.
[0017] The "impact mark" is a mark of impact force applied to the sintered body, preferably a mark formed on the sintered body by application of impact force. In other words, the impact mark is a mark of plastic deformation of the sintered body, that is, a mark of plastic deformation that occurs prior to destruction. Specific examples of the impact mark include a concave or concave portion, a concave portion, or a concave portion along the direction of application of the impact force in the impact core portion (described later).
[0018] In this embodiment, whether or not the sintered body has a plastic deformation region can be confirmed by applying an impact force (for example, a dynamic external force that advances the destruction of the sintered body) to the sintered body by any method. For example, by applying an impact force to the sintered body, and confirming the formation of an impact mark as a trace of plastic deformation (particularly, a trace of deformation prior to destruction) such as a recess or uneven portion on the sintered body after the impact force is applied, it can be confirmed that the sintered body has a plastic deformation region. In the sintered body of this embodiment, the impact mark is formed due to plastic deformation, but may include defects based on brittle fracture such as cracks that occur after (after the formation of the impact mark). On the other hand, if there are only defects based on brittle fracture such as cracks (i.e., only defects are confirmed without the formation of impact marks due to plastic deformation) or only deformation derived from destruction such as Hertzian destruction (i.e., only deformation formed by the development of destruction such as cracks that occurred initially) is confirmed, it can be determined that there is no plastic deformation region.
[0019] A preferred method for confirming the presence of a plastic deformation region is, for example, a ball drop test (hereinafter simply referred to as the "ball drop test") in which a DuPont ball drop tester conforming to JIS K 5600 5-3 is used to drop a weight from a specified height at room temperature.
[0020] FIG. 1 is a schematic diagram showing a ball drop test using a DuPont type ball drop tester. As shown in FIG. 1, in the ball drop test, a measurement sample (101) is attached with a protective tape (107) on the back side, placed on a cylindrical sample stage (106) of the ball drop tester, and fixed to the sample stage by attaching a fixing tape (105) to the side. The drop weight is composed of a weight (104) and a punch (102), and the punch (102) is placed on the surface of the measurement sample (101). The ball drop test can be performed by dropping the weight (104) from the punch from a height equivalent to the drop height (height corresponding to the double arrow in FIG. 1; 200 mm). The punch (102) has a cylindrical shape with a spherical (hemispherical) tip. A desired impact force can be applied to the measurement sample (101) via the striking die (102) by dropping a weight (104) along guides (103a, 103b) of the DuPont type ball drop tester.
[0021] FIG. 2 is a schematic diagram showing the appearance of the sintered body of this embodiment after the ball drop test. As shown in FIG. 2, it can be confirmed that the sintered body of this embodiment has an impact mark formed in the region where the impact force of the falling weight (striking die) was applied by the ball drop test (hereinafter, also referred to as the "impact core part"). The impact mark in FIG. 2 shows a state where a recess is formed near the impact core part, and it can be visually confirmed that it has a plastic deformation region. Although not shown, defects based on brittle fracture such as cracks may be present near the recess. In contrast, FIG. 3 is a schematic diagram showing the appearance of a conventional sintered body after the ball drop test. As shown in FIG. 3, the formation of an impact mark at the impact core part cannot be confirmed for the conventional sintered body, and only defects based on brittle fracture such as cracks are generated.
[0022] The presence or absence of a plastically deformed region may be confirmed by at least one of visual inspection and observation with an optical microscope, and more preferably by visual inspection. The magnification in the observation with an optical microscope is, for example, 1 to 100 times, and preferably 10 to 50 times.
[0023] Although not shown in the figure, conventional sintered bodies with high fracture toughness do not change in appearance before and after the ball drop test, and no impact marks can be confirmed. On the other hand, in sintered bodies having a plastic deformation region, plastic deformation occurs prior to brittle fracture. Therefore, when no impact marks can be confirmed, the ball drop test is repeated by increasing the drop height until the impact marks can be confirmed, and the presence or absence of a plastic deformation region can be confirmed by confirming the formation of impact marks such as the formation of recesses.
[0024] In order to evaluate the presence or absence of a plastic deformation region that has impact resistance acceptable for decorative parts such as the exterior materials of watches and portable electronic devices, in this embodiment, it is preferable to confirm the presence or absence of a plastic deformation region by a ball drop test in which a 300 g weight is dropped from a drop height of 200 mm.
[0025] The ball drop test in this embodiment can be performed at room temperature (20 to 30° C.) using a DuPont type ball drop tester conforming to JIS K 5600 5-3. The conditions for the ball drop test include the following.
[0026] Falling weight: (shape) Cylindrical stamping die with a spherical tip of 6.35 mm radius (mass) 300g Drop height: 200mm Measurement sample: A sintered body in the shape of a plate with dimensions of 40 mm length x 30 mm width x 2 mm thickness, with a surface roughness Ra of 0.02 μm or less on both surfaces To prevent the sample pieces from scattering, the measurement sample is placed on the sample stage of the ball drop tester by fixing one surface of the sample (40 mm long x 30 mm wide; main surface) with double-sided tape. After placement, fixation tape (protective tape) is applied vertically to the main surface that pairs with the surface on which the measurement sample is fixed, to fix the measurement sample in place (Figure 4). The ball drop test can then be carried out on the fixed measurement sample.
[0027] The depth of the impact mark formed by the ball drop test may be, for example, the depth [mm] (204 in Fig. 2) of the deepest part of the impact mark relative to the thickness [mm] (203 in Fig. 2) of the sintered body, which may be more than 0% and not more than 3.5%, furthermore, 0.05% to 3%, and furthermore, 0.1% to 3%. Note that the depth (204) of the impact mark (concave) in Fig. 2 is shown with the depth emphasized.
[0028] In this embodiment, the depth of the impact mark can be measured using a general laser microscope (e.g., VK-9500 / VK-9510, manufactured by Keyence Corporation) or a contact-type surface profiler (e.g., Dektak XTL, manufactured by Bruker Corporation). In the case of measurement using a laser microscope, the observation magnification can be, for example, 10 to 50 times, or even 20 times, and the laser wavelength can be, for example, 408 nm.
[0029] FIG. 5 is a schematic diagram showing an example of a method for measuring the depth of the impact mark. The method for measuring the depth of the impact mark is not limited to the method shown below. In this embodiment, the depth of the impact mark is measured by performing a line profile in the X-axis direction (503A), which is the maximum diameter direction of the impact mark formed in a substantially circular shape when viewed from above on the falling surface, and in the Y-axis direction (503B), which is perpendicular to the X-axis direction and extends within the falling surface, and measuring the difference between the height of the falling surface and the height of the impact mark surface in the Z-axis direction perpendicular to the X-axis and Y-axis, that is, the depth of the impact mark (504). The maximum depth measured along the X-axis direction is L1, the maximum depth measured along the Y-axis direction is L2, and the maximum depths are averaged (=(L1+L2) / 2), and the obtained length is taken as the depth of the impact mark of the sample. The measurement condition for measuring the length of the deepest part can be 0.5 μm / step, for example. Prior to the measurement, a standard sample (eg, a Si substrate with a pattern engraved thereon) with a known pattern length attached to the apparatus may be measured to adjust the analysis accuracy.
[0030] Such analyses such as line profile and measurement of the deepest part in the Z-axis direction can be performed by image analysis using analysis software attached to the laser microscope (for example, software name: VK-H1A9VK ANALYZER Version 3.0.1.0).
[0031] The sintered body of the present embodiment contains zirconia containing a stabilizing element and germanium oxide, and when the amount of the stabilizing element in the zirconia is X mol % and the amount of germanium oxide is Y mol %, Y / X is 0.35 or more and X+Y is 4.0 or less.
[0032] The sintered body of the present embodiment is a sintered body containing zirconia containing a stabilizing element, and is a sintered body having zirconia containing a stabilizing element as a main phase, that is, a so-called zirconia sintered body.
[0033] The stabilizing element has a function of stabilizing zirconia, and examples of the stabilizing element include one or more elements selected from the group consisting of calcium (Ca), magnesium (Mg), scandium (Sc), yttrium (Y), gadolinium (Gd), ytterbium (Yb), and dysprosium (Dy). Preferably, the stabilizing element is one or more elements selected from the group consisting of calcium (Ca), magnesium (Mg), yttrium (Y), gadolinium (Gd), and ytterbium (Yb), and more preferably, the stabilizing element is one or more elements selected from the group consisting of yttrium (Y) and gadolinium (Gd).
[0034] The content of the stabilizing element (hereinafter also referred to as "amount of stabilizing element") may be an amount that partially stabilizes zirconia. The amount of the stabilizing element is preferably 0.1 mol% or more, 0.2 mol% or more, 0.25 mol% or more, or 0.5 mol% or more, calculated as an oxide, and 4.0 mol% or less, 3.5 mol% or less, 3.0 mol% or less, or less than 3.0 mol%. In this embodiment, the amount of the stabilizing element is the ratio (mol%) of the total amount of the stabilizing element calculated as an oxide to the total amount of zirconia, the stabilizing element calculated as an oxide, and germanium oxide.
[0035] The sintered body of this embodiment contains germanium oxide. Germanium oxide (GeO2) may not be dissolved in zirconia, or may be at least partially dissolved in zirconia. The amount of germanium oxide is, in terms of oxide (GeO2), 0.1 mol%, 0.3 mol% or more, or 0.5 mol% or more, and 4.0 mol% or less, 3.5 mol% or less, 3.0 mol% or less, or less than 3.0 mol%. In this embodiment, the amount of germanium oxide is the ratio (mol%) of the total of germanium oxide to the total of zirconia, the stabilizing element in terms of oxide, and germanium oxide.
[0036] The Y / X ratio of the sintered body of this embodiment is 0.35 or more, preferably 0.45 or more, and more preferably 0.5 or more. Y / X is 4.0 or less, or 3.0 or less. These upper and lower limits may be in any combination.
[0037] The X+Y of the sintered body of this embodiment is 4.0 or less, preferably 3.5 or less, and more preferably 3.0 or less. X+Y may be 0.5 or more, or 1.0 or more. These upper and lower limits may be in any combination.
[0038] The sintered body of this embodiment may contain alumina (Al2O3). Since the sintered body of this embodiment may not contain alumina, the alumina content is 0 mass% or more. When alumina is contained, the alumina content may be more than 0 mass% and less than 30 mass%, preferably more than 0 mass% and 25 mass% or less, more preferably 0.005 mass% or more and 20 mass% or less. The alumina content may be 0 mass% or more, more than 0 mass%, 0.005 mass% or more, 0.05 mass% or more, or 0.25 mass% or more, and may be 30 mass% or less, 25 mass% or less, or 20 mass% or less. These upper and lower limits may be any combination. In terms of the ease with which the sintered body of this embodiment can obtain translucency, it is preferable that the sintered body of this embodiment does not contain alumina. On the other hand, from the viewpoint of the ease with which a dense sintered body can be obtained even at a relatively low temperature, the alumina content is preferably 0.05 mass% or more, and since the mechanical properties of the sintered body of this embodiment, such as mechanical properties such as static strength, tend to be high, the alumina content is preferably 30 mass% or less. The alumina content is the mass ratio of aluminum calculated as Al2O3 to the total amount of zirconia, stabilizing elements calculated as oxides, germanium oxide, and aluminum calculated as Al2O3.
[0039] The sintered body of this embodiment may contain a pigment component. The pigment component contained in the sintered body refers to a component that has the function of coloring the sintered body. This allows the sintered body to exhibit any color tone different from the original color tone of zirconia. The pigment component contained in the sintered body of this embodiment is at least one of an element and its compound that has the function of coloring zirconia, and is preferably, for example, a compound containing a rare earth element or a metal element, and further a transition metal element and a compound containing the same. As a specific pigment component, it is more preferable that it is one or more elements selected from the group consisting of vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu) and zinc (Zn), and a compound containing one or more of these, and it is even more preferable that it is an oxide containing one or more elements selected from the group consisting of manganese, iron, cobalt, nickel and zinc. As the pigment component, for example, by sintering a mixture of zirconia powder and pigment powder, a coloring element derived from the pigment powder or a compound containing the coloring element can be contained as a pigment component in the zirconia sintered body.
[0040] The pigment component in the sintered body of this embodiment may have any form, and may be contained as particles (second phase particles) or may be dissolved in zirconia.
[0041] The sintered body of this embodiment has a tendency that the smaller the content of the pigment component, the more likely it is that plastic deformation will occur. The content of the pigment component is preferably more than 0% by mass and 0.001% by mass or more. As long as the sintered body has a plastic deformation region, the content of the pigment component is arbitrary, but the content of the pigment component may be, for example, 10% by mass or less, less than 7.5% by mass, 5.0% by mass or less, 3.5% by mass or less, or 3.0% by mass or less. Any combination of these upper and lower limits may be used. The content of the pigment component can be determined as the ratio of the total mass of the pigment components converted into oxides to the mass of the sintered body of this embodiment. The oxide equivalent of the pigment component may be, for example, Co3O4 for cobalt, Fe2O3 for iron, Mn3O4 for manganese, and NiO for nickel. In addition, the content of the pigment component when the pigment component forms a complex oxide can be determined as the ratio of the total mass of the pigment components converted into complex oxides to the mass of the sintered body of this embodiment.
[0042] For example, when the sintered body of the present embodiment is a sintered body of zirconia containing a composite oxide represented by ABO3 or AB2O4, germanium oxide, and alumina as pigment components, and further containing yttrium and gadolinium as stabilizing elements, the content of each component may be determined as follows.
[0043] Pigment content [mass%] = {(ABO3+AB2O4) / (Y2O3+Gd2O3+ZrO2 +Al2O3+GeO2+ABO3+AB2O4)}×100 Alumina content [mass%] = {Al2O3 / (Y2O3+Gd2O3+ZrO2 +Al2O3+GeO2+ABO3+AB2O4)}×100 Germanium oxide [mol%] = {GeO2 / (GeO2+Y2O3+Gd2O3+ZrO2 )}×100 Stabilizing element amount [mol%]={(Y2O3+Gd2O3) / (Y2O3+Gd2O3+ZrO2)}×100 Amount of yttrium [mol%] = {(Y2O3) / (Y2O3+Gd2O3+ZrO2)}×100 Gadolinium content [mol%] = {(Gd2O3) / (Y2O3+Gd2O3+ZrO2)}×100 The sintered body of this embodiment preferably does not contain any impurities other than inevitable impurities. An example of the inevitable impurity is hafnia (HfO2). In addition, in the calculation of values related to the composition such as density in this embodiment, hafnia may be regarded as zirconia (ZrO2).
[0044] The color tone of the sintered body of the present embodiment is preferably white when it does not contain a pigment component. * a * b * ) Lightness in color space L * is preferably 70 or more, 75 or more, or 80 or more, and more preferably 80 or more. * can be calculated from the following formula:
[0045] C * ={(a * ) 2 +(b * ) 2} 0.5 Saturation C of the sintered body of this embodiment * When no pigment component is contained, it is preferably less than 10.0, less than 9.0, or less than 8.0, and more preferably less than 8.0. These upper and lower limits may be in any combination.
[0046] The color tone of the sintered body of the present embodiment is arbitrary when a pigment component is contained, but it is preferable that the color tone is in accordance with CIE1976(L * a * b * ) color space L * is between 0 and 95, a * is between -15 and 15, and b * is preferably −30 or more and 40 or less.
[0047] Lightness L * and chromaticity a *, b * The lightness L can be measured using a general spectrophotometer (e.g., CM-700d, manufactured by Konica Minolta) according to a method conforming to JIS Z 8722. * and chromaticity a * , b * The measurement conditions are as follows: It is preferable to perform the measurement using a black board as the background (so-called black back measurement).
[0048] Light source: D-65 light source Viewing angle: 10° Measurement method: SCI A disk-shaped sintered body with a diameter of 20 mm and a thickness of 1.8 mm is used as a measurement sample, and the surface to be evaluated is mirror-polished (Ra≦0.02 μm) to evaluate the color tone. The effective area for color tone evaluation is 10 mm in diameter.
[0049] The sintered body of this embodiment preferably has a high density, and more preferably has a density equivalent to a relative density of 98% or more, and more preferably 99% or more and 100% or less.
[0050] In this embodiment, the measured density can be calculated by Archimedes' method, and is a value calculated as a mass calculated by mass measurement relative to a volume calculated by Archimedes' method. In this embodiment, the relative density can be calculated from a ratio of the measured density to the theoretical density.
[0051] The zirconia contained in the sintered body of this embodiment is mainly composed of tetragonal crystals. Here, "zirconia is mainly composed of tetragonal crystals" means that 50% or more by volume of the zirconia crystal phase is tetragonal, and it is preferable that 50% or more by volume of the zirconia crystal phase of the sintered body of this embodiment is tetragonal, and 60% or more by volume of the zirconia crystal phase of the sintered body of this embodiment is tetragonal. Moreover, the zirconia contained in the sintered body of this embodiment may contain at least one of cubic crystals and monoclinic crystals.
[0052] The tetragonal ratio is the ratio of tetragonal zirconia to the zirconia crystal phase. The tetragonal ratio can be calculated from the powder X-ray diffraction pattern using the following formula.
[0053] f t =I t (111) / [I m (111)+I m (11-1)+I t (111)+I c (111)] × 100 In the above formula, f t is the tetragonal crystal ratio (%), I m (111) and I m (11-1) are the integrated intensities of the XRD peaks corresponding to the (111) and (11-1) planes of monoclinic zirconia, respectively, and I t (111) is the area intensity of the XRD peak corresponding to the (111) plane of tetragonal zirconia, and I c (111) is the integrated intensity of the XRD peak corresponding to the (111) plane of cubic zirconia.
[0054] In this embodiment, the powder X-ray diffraction pattern of the sintered body can be measured by a general X-ray diffraction device for crystallinity analysis (for example, device name: X'pert PRO MPD, manufactured by Spectris).
[0055] The measurement conditions are as follows:
[0056] Radiation source: CuKα radiation (λ=1.5418Å) Measurement mode: Continuous scan Scan speed: 4° / min Step width: 0.02° Measurement range: 2θ=26°~33° Tube voltage: 40kV Tube current: 40mA High-speed detector: X'Celerator + Ni filter The shape of the sintered body of the present embodiment may be at least one selected from the group consisting of a sphere, an approximately sphere, an ellipse, a disk, a cylinder, a cube, a rectangular parallelepiped, a polyhedron, and an approximately polyhedron. Furthermore, any shape may be used to achieve a desired purpose, such as various applications.
[0057] The sintered body of this embodiment preferably has a ball drop strength of 0.5 J or more, more preferably 0.6 J or more. The ball drop strength is an index of impact resistance, and the higher this value, the higher the impact resistance. Examples of the ball drop strength of the sintered body include 10 J or less, 7 J or less, and 5 J or less. These upper and lower limits may be in any combination.
[0058] Fall strength (J) = falling weight mass (g) x falling height (mm) x gravitational acceleration (m / s 2 ) The acceleration due to gravity is 9.8m / s 2 can be used.
[0059] The ball drop strength can be measured in the same manner as in the above-mentioned ball drop test, except that the ball is dropped from any height as shown below.
[0060] Drop height: 50~500mm The destruction can be judged as occurring when the measurement sample is divided into two or more pieces (Fig. 6(a)). On the other hand, when a crack occurs that does not reach from one end to the other end (Fig. 6(b)), it can be considered that destruction has not occurred. If destruction does not occur in the ball drop test at a specific drop height, the drop height can be increased by a fixed height (for example, 50 mm) up to 500 mm and the ball drop test can be repeated until destruction occurs, and visual observation can be performed in the same way. Alternatively, the weight of the drop weight can be changed instead of the drop height and the ball drop test can be repeated. For example, if destruction does not occur even when the drop height reaches 500 mm, the mass of the drop weight can be changed from 300 g to 500 g and the ball drop test can be performed again at a drop height of 500 mm, allowing measurement up to a higher ball drop strength.
[0061] An example of an index of the fracture resistance of the sintered body of this embodiment is the fracture toughness value. The fracture toughness value (MPa m 0.5 ) is 5.0 MPa m 0.5 or more than 6.0MPa m 0.5 and above 20.0MPa m 0.5 Less than or equal to 18.0MPa m 0.5 The following can be exemplified.
[0062] In this embodiment, the bending strength can be measured by a three-point bending test in accordance with JIS R 1601. The bending strength of the sintered body of this embodiment is preferably 100 MPa or more, and more preferably 300 MPa or more. In addition, the bending strength of the sintered body of this embodiment can be, for example, 1800 MPa or less, or 1600 MPa or less.
[0063] The sintered body of the present embodiment can be applied to the applications of conventional sintered bodies, particularly zirconia sintered bodies such as structural materials, optical materials, and dental materials, but can also be used as a member that requires relatively high impact resistance, such as decorative items, covers for accessories such as watches and housings, and exterior components for portable electronic devices such as mobile phones.
[0064] The method for producing the sintered body of this embodiment will be described below.
[0065] The sintered body of this embodiment may be produced by any method as long as it has the above-mentioned properties. An example of the method for producing the sintered body of this embodiment is a production method having a step of sintering a powder (hereinafter also referred to as a "raw material composition") containing a stabilizing element source, zirconia, and a germanium source. The powder may be subjected to the above-mentioned step (hereinafter also referred to as a "sintering step") in any form, and for example, it may be subjected to sintering after being formed into a molded body (compressed powder).
[0066] The stabilizing element source may be at least one of an oxide of the stabilizing element and a compound containing the stabilizing element as a precursor thereof, and may be at least one selected from the group consisting of oxides, hydroxides, oxychlorides, chlorides, acetates, nitrates, and sulfates as precursors of the oxides of the stabilizing element, and is preferably at least one of chlorides and nitrates. (Hereinafter, the stabilizing element sources when the stabilizing element is yttrium or gadolinium are also referred to as "yttrium source" and "gadolinium source", respectively.) The content of the stabilizing element source in the raw material composition may be equal to the amount of the stabilizing element in the target sintered body.
[0067] The yttrium source may be at least one of yttria (yttrium oxide; Y2O3) and its precursor yttrium compound, and may be one or more selected from the group consisting of yttrium chloride, yttrium, and yttrium carbonate, with yttrium chloride being preferred.
[0068] The gadolinium source may be at least one of gadolinia (gadolinium oxide) and a gadolinium compound that serves as a precursor thereof, and may include one or more selected from the group consisting of gadolinium chloride, gadolinium, and gadolinium carbonate, with gadolinium chloride being preferred.
[0069] The germanium source may be at least one of germanium oxide and a compound serving as a precursor thereof, and may be, for example, at least one selected from the group consisting of germanium hydroxide, chloride, alkoxide, nitrate, and sulfate, which serve as precursors of germanium oxide, and is preferably at least one selected from the group consisting of germanium oxide and its precursors, chloride, and alkoxide. The content of the germanium source in the raw material composition may be equal to the amount of stabilizing elements in the target sintered body.
[0070] The raw material composition may contain an alumina source. The alumina source is at least one of alumina (Al2O3) and a compound containing aluminum (Al) as a precursor thereof, and includes at least one selected from the group consisting of aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum hydroxide, alumina sol, and alumina, and is preferably alumina. The content of the alumina source in the raw material composition may be the same as the alumina content of the target sintered body.
[0071] The zirconia may be zirconium oxide (ZrO2), or may be zirconia containing a stabilizing element. Examples of zirconia containing a stabilizing element include yttrium-stabilized zirconia. When using zirconia containing a stabilizing element, any method may be used to make the zirconia contain the stabilizing element. For example, a hydrated zirconia sol is mixed with a stabilizing element source having a content equivalent to the desired stabilizing element, and the mixture is dried, calcined, and washed with water.
[0072] Furthermore, germanium oxide-containing stabilized zirconia containing germanium oxide and a stabilizing element may be used as the zirconia. Examples of germanium oxide-containing stabilized zirconia include germanium oxide-containing yttrium stabilized zirconia. When germanium oxide-containing stabilized zirconia is used, any method can be used to make zirconia contain germanium oxide. For example, a method of mixing a hydrated zirconia sol with a stabilizing element source and a germanium source, drying, calcining and washing with water, or a method of mixing a hydrated zirconia sol with a stabilizing element source, drying and calcining, and then mixing with a germanium source and calcining the mixture may be used.
[0073] Any mixing method may be used, and preferably at least one of dry mixing and wet mixing, more preferably wet mixing, and even more preferably wet mixing using a ball mill.
[0074] The method for producing a sintered body of the present embodiment may include a step of molding the raw material composition into a molded body (green compact) (hereinafter, also referred to as a "molding step").
[0075] The molded body may be produced by any method, and examples of the method include mixing zirconia, a stabilizing element source, a germanium source, and, if necessary, an additive such as an alumina source, by any method, and molding the mixture.
[0076] In order to improve the shape stability, the molded body may contain a binder. The binder may be any organic binder used in molding ceramics, and may be, for example, one or more selected from the group consisting of acrylic resin, polyolefin resin, wax, and plasticizer. The binder content may be, for example, 25% by volume or more and 65% by volume or less in the volume of the molded body at room temperature. Alternatively, the binder may be, for example, more than 0% by mass and 10% by mass or less in 100% by mass of the molded body.
[0077] The shape of the molded body may be any shape depending on the purpose, taking into consideration shrinkage due to sintering, and examples thereof include at least one selected from the group consisting of spherical, approximately spherical, elliptical, disk-like, cylindrical, cubic, rectangular, polyhedral, and approximately polyhedral.
[0078] The molding method may be a known molding method capable of converting the mixed powder into a green compact, and is preferably at least one selected from the group consisting of uniaxial pressing, isostatic pressing, injection molding, extrusion molding, rolling granulation, slip casting, and casting molding, more preferably at least one of uniaxial pressing and isostatic pressing, even more preferably at least one of cold isostatic pressing and uniaxial pressing (powder press molding), and even more preferably cold isostatic pressing after uniaxial pressing.
[0079] Prior to sintering, a step of calcining the molded body to obtain a calcined body (hereinafter, also referred to as a "calcining step") may be included. By calcining the molded body, the binder can be removed from the molded body.
[0080] The conditions for the calcination step may be any as long as the sintered body of this embodiment can be obtained, but an example of the condition is a heat treatment in air at 400° C. or higher and lower than 1100° C.
[0081] In the sintering step, the molded body is sintered to obtain a sintered body. Any sintering method can be used as long as the sintering proceeds, and examples of such methods include known sintering methods such as atmospheric sintering, pressure sintering, and vacuum sintering. As a preferred sintering method, atmospheric sintering is used, and since it is simple, it is preferable to use only atmospheric sintering. This allows the sintered body of this embodiment to be obtained as a so-called atmospheric sintered body. The atmospheric sintering method is a method in which no external force is applied to the molded body (or the calcined body) during sintering, and the sintered body is sintered by simply heating it. Note that the composition of the germanium oxide-containing stabilized zirconia does not change during the sintering process. In other words, the composition of the germanium oxide-containing stabilized zirconia powder, the calcined body of the germanium oxide-containing stabilized zirconia, and the sintered body of the germanium oxide-containing stabilized zirconia may be considered to be the same.
[0082] The conditions of normal pressure sintering include a sintering temperature of 1050°C to 1600°C, preferably 1100°C to 1550°C, 1100°C to 1500°C, or 1150°C to 1500°C. The sintering atmosphere may be at least one of an air atmosphere and an oxygen atmosphere, and preferably an air atmosphere. The heating rate may be 20°C / hour to 5000°C / hour. The sintering time may be appropriately set according to the amount and size of the sintered material to be sintered and the characteristics of the sintering furnace, and may be, for example, held at the above sintering temperature for 0.3 hours to 20 hours, 0.5 hours to 20 hours, or 0.5 hours to 15 hours.
[0083] Any method for producing zirconia may be used in the method for producing the sintered body of the present embodiment. One example of the method for producing zirconia includes a method including a step of heat-treating a composition containing a zirconia sol containing crystalline zirconia whose main phase is monoclinic zirconia and a stabilizing element source at 600° C. to 1250° C. to obtain a calcined powder, and a step of pulverizing the calcined powder.
[0084] The manufacturing method will be specifically described below, but the manufacturing method of zirconia in this embodiment is not limited thereto.
[0085] The method for producing the zirconia sol containing crystalline zirconia whose main phase is monoclinic zirconia is arbitrary, and at least one of hydrothermal synthesis and hydrolysis can be exemplified. In the hydrothermal synthesis, a coprecipitate obtained by mixing a zirconium salt with an alkali or the like in the presence of a solvent is heat-treated at 100 to 200°C to obtain a zirconia sol. In the hydrolysis, a zirconium salt is heated in the presence of a solvent to hydrolyze the zirconium salt, thereby obtaining a zirconia sol. Thus, the zirconia sol can be exemplified as a zirconia sol obtained by a hydrothermal synthesis or hydrolysis, and is preferably a zirconia sol obtained by a hydrolysis. A zirconium salt can be exemplified as a precursor used in the method for producing a zirconia sol. The zirconium salt can be one or more selected from the group consisting of zirconium oxychloride, zirconium nitrate, zirconium chloride, and zirconium sulfate, and is preferably at least one of zirconium nitrate and zirconium oxychloride, and more preferably zirconium oxychloride.
[0086] A calcined powder, which is a precursor of zirconia powder, is obtained by a process in which a composition (zirconia raw material composition) containing a zirconia sol containing zirconia whose main phase is monoclinic zirconia and a stabilizing element source is heat-treated at 600° C. or more and 1250° C. or less to form a calcined powder (hereinafter also referred to as a "powder calcination process").
[0087] In the powder calcination step, the heat treatment is performed at 500°C or more and 1250°C or less, and further at 600°C or more and 1250°C or less. By performing the heat treatment at 600°C or more, a powder that is easily densified by normal pressure sintering can be obtained. On the other hand, by performing the heat treatment at 1250°C or less, a powder that is easily dispersed by pulverization can be obtained. The heat treatment time may be appropriately changed depending on the heat treatment temperature, the amount of the zirconia raw material composition to be subjected to the treatment, and the characteristics of the heat treatment furnace, and may be, for example, 30 minutes to 6 hours. The rate of temperature rise to the heat treatment temperature has almost no effect on the calcined powder obtained, and the rate of temperature rise may be, for example, 50°C / hour to 1000°C / hour.
[0088] The heat treatment may be performed in any atmosphere, for example, any atmosphere selected from the group consisting of an oxidizing atmosphere, a reducing atmosphere, an inert atmosphere, and a vacuum atmosphere. An oxidizing atmosphere is preferable, and an air atmosphere is more preferable.
[0089] The zirconia raw material composition to be subjected to the powder calcination step may contain the above-mentioned zirconia sol and the stabilizing element source, and all or a part of the stabilizing element source may be dissolved in the zirconia sol. For example, at least a part of the stabilizing element source may be dissolved in the zirconia sol by a method such as mixing a zirconium salt and the stabilizing element source and hydrolyzing the mixture, or mixing a zirconium salt, the stabilizing element source, and an alkali to form a coprecipitate.
[0090] In the pulverization process, the calcined powder is pulverized. Zirconia with a low content of stabilizing elements is prone to cracking and chipping during sintering. In contrast, pulverizing the calcined powder tends to increase the yield during sintering.
[0091] The grinding method may be any method, and may be at least one of wet grinding and dry grinding, preferably wet grinding, more preferably wet grinding using an aqueous dispersion medium with a pH of < 7.0 (i.e., acidic), and more preferably wet grinding using an aqueous dispersion medium with a pH of < 5.0. Specific examples of wet grinding include one or more selected from the group consisting of a ball mill and a continuous media stirring mill, and preferably a ball mill.
[0092] The powder to be subjected to the pulverization step may be a calcined powder or a mixed powder containing the calcined powder, a germanium source, and an alumina source. The germanium source may be the above-mentioned germanium source, and the alumina source may be the above-mentioned alumina source.
[0093] The conditions for pulverization using a ball mill include, for example, mixing the calcined powder with a solvent (e.g., at least one of water and alcohol, and further water) to form a slurry in which the mass ratio of the calcined powder to the mass of the slurry is 30% by mass or more and 60% by mass or less, and pulverizing the slurry using zirconia balls having a diameter of 0.5 mm to 15 mm as a pulverization medium. The pulverization time may be appropriately adjusted depending on the amount of the calcined powder to be subjected to the treatment, and may be, for example, 8 hours to 100 hours.
[0094] After the wet grinding, the mixture is dried by any method to obtain zirconia powder. Drying conditions include air atmosphere and 110°C to 130°C.
[0095] In order to improve the handling of the powder, the manufacturing method of the powder may include a step of granulating the powder (hereinafter, also referred to as a "granulation step"). Any method may be used for granulation, and an example is spray granulation of a slurry in which the powder is mixed with a solvent. The solvent is at least one of water and alcohol, and preferably water. The granulated powder (hereinafter, also referred to as "powder granules") has an average granule diameter of 30 μm to 80 μm, and furthermore, 50 μm to 60 μm, and a bulk density of 1.00 g / cm. 3 More than 1.50g / cm 3 Below that, 1.10g / cm3 More than 1.45g / cm 3 The following are some of the reasons: EXAMPLES
[0096] The present embodiment will be described below using examples, but the present embodiment is not limited thereto.
[0097] (Confirmation of plastic deformation area) The presence or absence of plastic deformation regions in the sintered samples was confirmed by a ball drop test using a DuPont ball drop tester (H-50, manufactured by Toyo Seiki Co., Ltd.) conforming to JIS K 5600 5-3. The test conditions are as follows:
[0098] Falling weight: (shape) Cylindrical stamping die with a spherical tip of 6.35 mm radius (Mass) 300g, i.e. made of SUS, width 80mm x thickness 20mm A rectangular parallelepiped weight of 300 g and measuring 30 mm x 30 mm in height Drop height: 200mm Measurement sample: A plate measuring 40 mm long x 30 mm wide x 2 mm thick, with both surfaces ( A sintered body with a surface roughness of Ra≦0.02μm (main surface, 40mm long × 30mm wide) In order to prevent the sample pieces from scattering, the measurement sample was placed on the sample stage of the ball drop tester by fixing one surface of the measurement sample (a surface measuring 40 mm long x 30 mm wide) with double-sided tape. After placement, tape was applied vertically to the surface opposite the fixed surface of the measurement sample to fix the measurement sample. The hitting mold was placed so that the falling weight would fall near the center of the fixed measurement sample, and the ball drop test was performed.
[0099] (Measurement of ball drop strength) The ball drop strength was measured in the same manner as the ball drop test for confirming the plastic deformation region, except for changing the ball drop height. That is, the state of the test specimen after the drop of the weight was visually confirmed, and the ball drop strength at the ball drop height at which the test specimen was broken was calculated from the following formula.
[0100] Fall strength (J) = Mass of falling weight (g) x Fall height (mm) x Gravitational acceleration (9.8m / s 2 ) The test specimen was deemed to have been broken when it was broken into two or more pieces. However, a test specimen that maintained its plate-like shape while minute chipping-like fragments were generated was not deemed to have been broken. If no breakage occurred in the test at a specific drop height, the test was repeated with the drop height increased by 50 mm from 50 mm to 500 mm until breakage occurred. If no breakage occurred even when the drop height reached 500 mm, the mass of the drop weight was changed from 300 g to 500 g, and from 500 g to 1 kg, and the test was repeated at a drop height of 500 mm. For the sake of convenience, the drop strength of test specimens that did not break in the test at a drop height of 500 mm with a drop weight of 1 kg was determined to be >5J (more than 5J).
[0101] (density) The measured density of a sintered sample is the ratio of the volume measured by Archimedes' method to the mass measured by mass measurement (g / cm 3 Prior to the measurement, the mass of the dried sintered body was measured, and then the sintered body was placed in water and boiled for 1 hour as a pretreatment. Theoretical density (g / cm 3 ) is calculated assuming that the crystal phase of the zirconia in the sintered body is entirely tetragonal, and the unit cell volume (cm) of the zirconia 3 ) was calculated from the unit cell mass (g) for
[0102] (Fracture toughness) The fracture toughness of the sintered samples was measured by a method conforming to the SEPB method specified in JIS R 1607.
[0103] (Bending strength) The bending strength of the sintered samples was measured by a three-point bending test according to JIS R 1601.
[0104] (Color Tone Measurement) The color tone of the sintered body samples was measured according to the method of JIS Z 8722. For the measurement, a general spectrophotometer (device name: CM-700d, manufactured by Konica Minolta) was used, and the measurement was performed against a black background using a black plate on the back. The measurement conditions were as follows.
[0105] Light source: D-65 light source Viewing angle: 10° Measurement method: SCI The sintered body sample used was a disk-shaped sample with a diameter of 20 mm and a thickness of 1.8 mm. One surface of the sintered body sample was mirror-polished (Ra≦0.02 μm), and the color tone was evaluated using this surface as the evaluation surface. The effective area for color tone evaluation was 10 mm in diameter.
[0106] Example 1 A hydrated zirconia sol was obtained by hydrolysis of an aqueous zirconium oxychloride solution. Yttrium chloride hexahydrate was added to and mixed with the hydrated zirconia sol so that the yttrium concentration was 1.0 mol%. After mixing, the mixture was dried in an air atmosphere and calcined at 1000°C in an air atmosphere for 2 hours to obtain calcined yttrium-stabilized zirconia powder. The calcined powder obtained was washed with pure water, and then germanium oxide powder was added and wet-mixed so that the germanium oxide concentration was 2.4 mol% to obtain a mixed powder. The mixed powder was dried in an air atmosphere and calcined at 800°C in an air atmosphere for 2 hours to obtain a zirconia powder consisting of germanium oxide-containing yttrium-stabilized zirconia.
[0107] The obtained zirconia powder was mixed with pure water to which hydrochloric acid had been added so that the pH was 2 to obtain a slurry, which was then ground and mixed for 24 hours in a ball mill using zirconia balls as a grinding medium. The ground and mixed slurry was dried at 110°C in an air atmosphere, and coarse particles having an aggregate diameter exceeding 180 μm were removed by sieving to obtain a powder consisting of germanium oxide-containing yttrium-stabilized zirconia with a germanium oxide content of 2.4 mol% and an yttrium oxide content of 1.0 mol%.
[0108] The powder of this example was subjected to uniaxial pressing at a pressure of 50 MPa and cold isostatic pressing (CIP) at a pressure of 196 MPa to form a green body. The obtained green body was calcined under the following conditions.
[0109] Calcination method: Normal pressure calcination Calcination atmosphere: Air Calcining temperature: 700℃ Pre-baking time: 1 hour Thereafter, the sintered body of this example, which is made of germanium oxide-containing yttrium-stabilized zirconia and has a germanium oxide content of 2.4 mol % and a yttrium oxide content of 1.0 mol %, was obtained by sintering under the following conditions. The sintering conditions are shown below.
[0110] Sintering method: Pressureless sintering Sintering atmosphere: Air Sintering temperature: 1300℃ Sintering time: 2 hours Example 2: A powder containing germanium oxide-containing yttrium-stabilized zirconia was obtained, which contained 10 mass% alumina for zirconia having a germanium oxide content of 2.0 mol% and an yttrium oxide content of 1.0 mol%, using the same method as in Example 1, except that the amount of germanium oxide added was 2.0 mol% and 10 mass% alumina powder was mixed into the slurry during grinding and mixing.
[0111] A sintered body of this example was obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1350°C.
[0112] Example 3 A powder containing germanium oxide-containing yttrium-stabilized zirconia was obtained, which contained 20 mass% alumina for zirconia having a germanium oxide content of 2.0 mol% and an yttrium oxide content of 1.0 mol%, using the same method as in Example 1, except that the amount of germanium oxide added was 2.0 mol% and 20 mass% alumina powder was mixed into the slurry during grinding and mixing.
[0113] A sintered body of this example was obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1400°C.
[0114] Example 4 A hydrated zirconia sol was obtained by hydrolysis of an aqueous solution of zirconium oxychloride. Yttrium chloride hexahydrate was added and mixed with the hydrated zirconia sol so that the yttrium concentration was 1.2 mol%. After mixing, the mixture was dried in an air atmosphere and calcined at 1000°C for 2 hours in an air atmosphere to obtain a calcined yttrium-stabilized zirconia powder.
[0115] The obtained zirconia powder was mixed with 1.1 mol% germanium oxide, 10 mass% alumina based on the total solid content, and pure water to which hydrochloric acid was added so that the pH was 2 to obtain a slurry, which was then ground and mixed for 24 hours in a ball mill using zirconia balls as a grinding medium. The ground and mixed slurry was dried at 110°C in an air atmosphere, and coarse particles having an aggregate diameter exceeding 180 μm were removed by sieving to obtain a powder containing germanium oxide-containing yttrium-stabilized zirconia containing 10 mass% alumina for zirconia with a germanium oxide content of 1.1 mol% and an yttrium oxide content of 1.2 mol%.
[0116] A sintered body of this example was obtained in the same manner as in Example 1, except that the powder was used.
[0117] Example 5 A powder containing germanium oxide-containing gadolinium-stabilized zirconia was obtained, containing 10 mass% alumina for zirconia having a germanium oxide content of 1.8 mol% and a gadolinium oxide content of 1.2 mol%, by the same method as in Example 1, except that 1.2 mol% gadolinium chloride was added instead of yttrium chloride, the amount of germanium oxide added was 1.8 mol%, and 10 mass% alumina powder was mixed into the slurry during grinding and mixing.
[0118] A sintered body of this example was obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1350°C.
[0119] Example 6 A powder containing germanium oxide-containing gadolinium-stabilized zirconia was obtained in the same manner as in Example 3, except that 1.2 mol% gadolinium chloride was added instead of yttrium chloride and the amount of germanium oxide added was 1.2 mol%. The powder contained 10 mass% alumina for zirconia having a germanium oxide content of 1.2 mol% and a gadolinium oxide content of 1.2 mol%.
[0120] A sintered body of this example was obtained in the same manner as in Example 1, except that the powder was used. Example 7 A powder containing germanium oxide-containing gadolinium-stabilized zirconia was obtained in the same manner as in Example 4, except that yttrium chloride hexahydrate was added so that the yttrium concentration was 1.5 mol%, the amount of germanium oxide added was 0.7 mol%, and the amount of alumina added was 0.25 mass%. The powder contained 0.25 wt% alumina for zirconia having a germanium oxide content of 0.7 mol% and an yttrium content of 1.5 mol%.
[0121] A sintered body 1 of this example was obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1250° C. In addition, a sintered body 2 of this example was obtained in the same manner as described above, except that the sintering temperature was set to 1450° C. The two types of sintered bodies 1 and 2 produced using the powder of this example are respectively referred to as Example 7-1 and Example 7-2 in Table 2 described later.
[0122] Comparative Example 1 A zirconia powder consisting of yttrium-stabilized zirconia with an yttrium oxide content of 2.0 mol% was obtained in the same manner as in Example 1, except that yttrium chloride hexahydrate was added so that the yttrium concentration was 2.0 mol% and germanium oxide was not added.
[0123] A sintered body of this comparative example was obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1450°C.
[0124] Comparative Example 2 A zirconia powder consisting of cerium- and yttrium-stabilized zirconia with an yttrium oxide content of 1.0 mol% and a cerium oxide content of 4.0 mol% was obtained in the same manner as in Example 1, except that cerium chloride heptahydrate was added so that the ceria concentration was 4.0 mol% and germanium oxide was not added.
[0125] A sintered body of this comparative example was obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1450°C.
[0126] Comparative Example 3 A powder containing germanium oxide-containing yttrium-stabilized zirconia was obtained in the same manner as in Example 4, except that yttrium chloride hexahydrate was added so that the yttrium concentration was 3.0 mol%, the amount of germanium oxide added was 0.3 mol%, and the amount of alumina added was 0.25 mass%. The powder contained 0.25 mass% alumina for zirconia having a germanium oxide content of 0.3 mol% and an yttrium oxide content of 3.0 mol%.
[0127] A sintered body of this example was obtained in the same manner as in Example 1, except that the powder was used and the sintering temperature was set to 1200°C.
[0128] The compositions of the sintered bodies of these examples and comparative examples are shown in Table 1, and the evaluation results are shown in Table 2.
[0129] [Table 1] TIFF0007662009000002.tif58132
[0130] It can be seen from the above table that the powders of Examples 1 to 7 contain germanium oxide, and that the ratio (Y / X) of the germanium oxide content to the stabilizing element content of the zirconia powder is 0.35 or more.
[0131] [Table 2]
[0132] In the above table, the "Formation of Impact Mark" column indicates that impact marks were confirmed after the ball drop test with a "◯" and that no impact marks were confirmed with an "X". Figure 7 shows the appearance of the sintered body of Example 2 after the ball drop test. Figure 7 shows that the area where the falling weight came into contact in the ball drop test formed an impact mark (depression) without any destruction such as cracks, that is, it can be visually confirmed that the impact mark (depression) is a trace of plastic deformation.
[0133] The sintered bodies of Examples 1 to 6 all had a tetragonal ratio of more than 60%, and were confirmed to be mainly composed of tetragonal crystals. Impact marks as traces of plastic deformation could be visually confirmed, and the falling ball fracture energy was 1.0 J or more. Impact marks as traces of plastic deformation, similar to those in FIG. 7, could be visually confirmed for these sintered bodies.
[0134] It was confirmed that the sintered body of Comparative Example 1, which contained only yttrium as a stabilizing element, had lower fracture toughness and falling ball fracture energy than Examples 1-6.
[0135] In addition, from the above table, Examples 1 to 6 are L * Value is 80 or more and a * value and b * The absolute value of the value was 5 or less, and the sintered body was white in color. The sintered body of Comparative Example 2, which contained CeO2 as a stabilizing element, had impact marks as traces of plastic deformation that could be visually confirmed, and had a high falling ball fracture energy. * Value is less than 80 and a * value and b *The absolute value of the value was greater than 5.0, and the color was yellow due to ceria.
[0136] From the above, it was confirmed that all of the sintered bodies of the above examples had high impact resistance and fracture toughness and were free of coloration derived from ceria.
[0137] Example 8 A hydrated zirconia sol was obtained by hydrolysis of an aqueous zirconium oxychloride solution. Yttrium chloride hexahydrate was added to and mixed with the hydrated zirconia sol so that the yttrium concentration was 1.6 mol%. After mixing, the mixture was dried in an air atmosphere and calcined at 1000°C for 2 hours in an air atmosphere to obtain a calcined yttrium-stabilized zirconia powder. The calcined powder obtained was washed with pure water, and then germanium oxide, alumina, and cobalt oxide were added so that the germanium oxide concentration was 1.0 mol%, the alumina content was 0.25 mass%, and the cobalt oxide content was 1.0 mass%, and pure water was added to make a slurry, which was then pulverized and mixed in a ball mill using zirconia balls as a milling medium. The slurry after grinding and mixing was dried at 110°C in an air atmosphere, and then coarse particles having an agglomeration diameter exceeding 180 µm were removed by sieving to obtain a powder of this example containing germanium oxide-containing yttrium-stabilized zirconia, which contains 0.25 mass% alumina and 1.0 mass% cobalt oxide with respect to zirconia powder having a germanium oxide content of 1.0 mol% and an yttrium oxide content of 1.6 mol%.
[0138] The powder of this example was uniaxially pressed at a pressure of 50 MPa and then subjected to cold isostatic pressing (CIP) at a pressure of 196 MPa to form a compact. The resulting compact was calcined under the following conditions to obtain the calcined body of this example.
[0139] Calcination method: Normal pressure calcination Calcination atmosphere: Air Calcining temperature: 700℃ Pre-baking time: 1 hour Then, the mixture was sintered under the following conditions to obtain a sintered body of this example containing zirconia with a germanium oxide content of 1.0 mol % and a yttrium oxide content of 1.6 mol %, 0.25 mass % alumina, and 1.0 mass % cobalt oxide. The sintering conditions are as follows:
[0140] Sintering method: Pressureless sintering Sintering atmosphere: Air Sintering temperature: 1400℃ Sintering time: 2 hours Example 9 A powder and a calcined body of this example containing 0.25 mass % alumina and 1.0 mass % iron oxide for zirconia having a germanium oxide content of 0.6 mol % and an yttrium oxide content of 1.6 mol % were obtained in the same manner as in Example 8, except that the amount of germanium oxide added was 0.6 mol % and iron oxide (Fe2O3) was used instead of cobalt oxide (Co3O4) as the pigment component.
[0141] A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1350°C. Example 10 The powder and calcined body of this example were obtained in the same manner as in Example 7, except that yttrium chloride hexahydrate was added so that the yttrium concentration was 1.2 mol%, the amount of germanium oxide added was 1.2 mol%, alumina was not added, and 0.5 mass% of CoAl2O4 was used instead of cobalt oxide (Co3O4) as the pigment component. The powder and calcined body of this example contained 0.5 mass% CoAl2O4 for zirconia with a germanium oxide content of 1.2 mol% and an yttrium oxide content of 1.2 mol%.
[0142] The sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1250°C. Example 11 The powder, calcined body and sintered body of this example were obtained by using a zirconia powder having a germanium oxide content of 1.2 mol% and an yttrium oxide content of 1.2 mol% and containing 10 mass% alumina, 0.03 mass% iron oxide and 0.01 mass% CoAl2O4, in addition to CoAl2O4 as a pigment component, in the same manner as in Example 10, except that 0.03 mass% iron oxide (Fe2O3) was added in addition to CoAl2O4 as a pigment component, 10 mass% alumina was added, and the amount of CoAl2O4 added was 0.01 mass%.
[0143] A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1250°C. Example 12 The powder and calcined body of this example were obtained by using zirconia having a germanium oxide content of 2.0 mol% and an yttrium oxide content of 1.0 mol%, with the exception that yttrium chloride was added so that the yttrium concentration was 1.0 mol%, and the amount of germanium oxide added was 2.0 mol%. The powder and calcined body of this example contained 10 mass% alumina, 0.03 mass% iron oxide, and 0.01 mass% CoAl2O4. A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1250°C. Example 13 A powder and calcined body of this example containing 1.0 mass% NiO for zirconia having a germanium oxide content of 1.2 mol% and a gadolinium oxide content of 1.4 mol% were obtained in the same manner as in Example 9, except that gadolinium chloride was added instead of yttrium chloride so that the gadolinium concentration was 1.4 mol%, and 1 mass% nickel oxide (NiO) was added instead of CoAl2O4.
[0144] A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1200°C. Example 14 A powder and calcined body of this example containing 1.0 mass% manganese oxide for zirconia with a germanium oxide content of 0.7 mol%, yttrium oxide content of 0.4 mol%, and gadolinium oxide content of 1.4 mol% were obtained in the same manner as in Example 12, except that yttrium chloride was added in addition to gadolinium chloride so that the yttrium concentration was 0.4 mol%, the amount of germanium oxide added was 0.7 mol%, and 1 mass% manganese oxide (Mn3O4) was added instead of nickel oxide. A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1200°C. Example 15 A powder and calcined body of this example containing 10 mass% alumina, 0.3 mass% iron oxide, 1.0 mass% manganese oxide, and 0.3 mass% cobalt oxide for zirconia having a germanium oxide content of 1.2 mol%, yttrium oxide content of 0.4 mol%, and gadolinium oxide content of 1.4 mol% were obtained in the same manner as in Example 14, except that the amount of germanium oxide added was 1.2 mol%, and that in addition to 1 mass% manganese oxide, 10 mass% alumina, 0.3 mass% iron oxide, 1.0 mass% manganese oxide, and 0.3 mass% cobalt oxide were added.
[0145] A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1350°C. Example 16 The powder and calcined body of this example were obtained in the same manner as in Example 15, except that yttrium chloride was added so that the yttrium concentration was 1.6 mol%, gadolinium chloride was not added, and the amount of germanium oxide added was 0.6 mol%. The powder and calcined body of this example contained 10 mass% alumina, 0.3 mass% iron oxide, 1.0 mass% manganese oxide, and 0.3 mass% cobalt oxide relative to zirconia having a germanium oxide content of 0.6 mol% and an yttrium oxide content of 1.6 mol%.
[0146] A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used. Example 17 A powder and calcined body of this example containing 0.25 mass% alumina, 0.01 mass% iron oxide, 0.5 mass% manganese oxide, and 0.6 mass% CoAl2O4 relative to zirconia having a germanium oxide content of 0.8 mol% and an yttrium oxide content of 2.0 mol% were obtained in the same manner as in Example 8, except that yttrium chloride was added so that the yttrium concentration was 2.0 mol%, the amount of germanium oxide added was 0.8 mol%, and instead of adding 1 mass% cobalt oxide, 0.01 mass% iron oxide, 0.5 mass% manganese oxide, and 0.6 mass% CoAl2O4 were added.
[0147] A sintered body of this example was obtained in the same manner as in Example 8, except that the powder was used and the sintering temperature was set to 1450°C.
[0148] The compositions of the sintered bodies of these Examples and Comparative Examples are shown in Table 3, and the evaluation results are shown in Table 4.
[0149] [Table 3]
[0150] From the above table, it can be seen that the powders of Examples 8 to 17, like the powders in Table 1, contain germanium oxide, and the ratio (Y / X) of the germanium oxide content to the stabilizing element content of the zirconia powder is 0.35 or more.
[0151] [Table 4]
[0152] From the above table, it was confirmed that the sintered bodies of Examples 8 to 17 exhibited a color tone different from white due to the addition of a pigment component, and were capable of exhibiting a desired color tone without the influence of coloring derived from ceria. In addition, impact marks as traces of plastic deformation could be visually confirmed for the sintered bodies of Examples 8 to 17, and the falling ball fracture energy was 1.0 J or more. [Explanation of symbols]
[0153] 100: Overview of the drop ball test 101: Sintered body 102: Punch 103a, 103b: Guide 104: Falling weight 105: Fixing tape 106: Sample stand for the ball drop test machine 107: Protective tape 200: Sintered body of this embodiment after drop test 201: Sintered body 202: Impact mark (dent) 203: Depth of impact mark (dent) 300: Conventional sintered body after drop test 301: Sintered body 302: Defect (crack) 400: A diagram showing the placement of a sintered compact on the sample stage of a drop test machine. 401: Sintered body 402: Fixing tape 403: Sample stand for the ball drop test machine 404: Double-sided tape (protective tape) 500: Diagram showing how to measure impact mark depth 501: Sintered body 502: Impact mark (dent) 503A,B: Line profile 504: Depth of impact mark 601: Sintered body in a divided state 602: Defect (crack) 702: Impact mark (dent)
Claims
1. A sintered body which comprises zirconia containing a stabilizing element, which comprises germanium oxide, the stabilizing element comprising at least one selected from the group consisting of yttrium and gadolinium, wherein when the amount of the stabilizing element in the zirconia is X mol % in terms of oxide and the amount of the germanium oxide is Y mol %, Y / X is 0.35 or more and 4.0 or less, and which undergoes plastic deformation when a load is applied.
2. A sintered body as described in claim 1, which has a lightness L* in the CIE 1976 (L*a*b*) color space of 70 or more, 75 or more, or 80 or more.
3. The sintered body according to claim 1, containing one or more elements selected from the group consisting of vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu) and zinc (Zn), and a compound containing one or more of these elements.
4. 3. The sintered body according to claim 1, wherein the germanium oxide content is 0.1 mol % or more and less than 4.0 mol %.
5. 3. The sintered body according to claim 1, wherein the stabilizing element comprises at least one selected from the group consisting of yttrium, calcium, magnesium, ytterbium, and gadolinium.
6. 3. The sintered body according to claim 1, wherein the content of the stabilizing element is 0.1 mol % or more and 4.0 mol % or less.
7. The fracture toughness value measured by the method based on the SEPB method specified in JIS R1607 is 6.0 MPa m 0.5 The sintered body according to claim 1 or 2.
8. The sintered body according to claim 1 or 2, which contains alumina.
9. 3. A method for producing a sintered body according to claim 1 or 2, characterized in that a powder containing zirconia containing a stabilizing element, containing germanium oxide, the stabilizing element containing at least one selected from the group consisting of yttrium and gadolinium, and having a Y / X ratio of 0.35 or more when the amount of the stabilizing element in the zirconia is X mol % in terms of oxide and the amount of the germanium oxide is Y mol %, is sintered at 1100° C. or more and 1500° C. or less for 0.3 hours or more and 20 hours or less.
10. 3. A method for producing a sintered body according to claim 1 or 2, comprising sintering a powder containing zirconia containing a stabilizing element, containing germanium oxide, the stabilizing element containing at least one selected from the group consisting of yttrium and gadolinium, in which, when the amount of the stabilizing element in the zirconia is X mol % and the amount of the germanium oxide is Y mol %, X + Y is 4.0 or less, at 1100° C. or more and 1500° C. or less for 0.3 hours or more and 20 hours or less.
11. A member comprising the sintered body according to claim 1 or 2.
Citation Information
Patent Citations
Zirconia ceramics
JP1992349172A
Sintered body, powder, and method for producing the same
JP2021088501A
Sintered body having excellent impact resistance
JP2021091601A
Sintered body having excellent impact resistance
JP2021091602A
Sintered body and method for producing same
WO2021215419A1